Front Cover: Efficient Synthesis of Benzothiazinone Analogues with Activity against Intracellular Mycobacterium tuberculosis (ChemMedChem 6/2022). (18th March 2022) - Richter, Adrian; Narula, Gagandeep; Rudolph, Ines; Seidel, Rüdiger W.; Wagner, Christoph; Av‐Gay, Yossef; Imming, Peter
Abstract : The Front Cover shows a synthetic step and example molecule of one of the most toxic compounds against the single most lethal bacterial pathogen, Mycobacterium tuberculosis, depicted microscopically in human macrophages and macroscopically on a culture plate. The beauty of the bacterial colonies is deceptive as it causes the White Plague aka Consumption aka Tuberculosis. The molecule is a benzothiazinone (BTZ), a substance class first published as strongly antimycobacterial in 2009. The article by Richter et al. in this issue focuses on a new synthetic pathway to BTZs. More information can be found in the Research Article by Adrian Richter, Peter Imming et al.